Feeding habits of Antarctic Eocene penguins from a morphofunctional perspective - Haidr, Nadia Soledad; Acosta Hospitaleche, Carolina Ileana Alicia (Neues Jahrbuch für Geologie und Paläontologie - Abhandlungen)
Cranial and mandibular penguin remains from the Eocene of Antarctica were studied in order to determine their feeding habits and food item preferences. Their osteology and musculature were compared with those of modern taxa. Different morphotypes were recognized based on their skull, configuration of the articular region of the mandible and bill shape. The results point to a variety of trophic habits and food preferences consistent with the known taxonomic diversity for this unit. For the middle Eocene, large sized penguins were interpreted as fish and crustacean eaters, whereas for the late Eocene, taxonomic diversity and number of individuals in the colonies during the late Eocene seems to increase. This colony could be reconstructed as being composed of medium-sized generalist penguins, piscivorous large- and medium-sized species, and also large penguins with a diet based on crustaceans and squids. Fil: Haidr, Nadia Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina